Realitet på spill: Iscenesettelse av det reelle i teater og teaterpedagogikk - Hustvedt, Kjersti (Peripeti, 2011)
Hustvedt analyses and discusses two different theatre pedagogical strategies for the staging of so called “everyday experts” and their reality; on the one hand a self-reflexive strategy where the everyday reality is staged as a construction, on the other hand an authenticity strategy where the staged reality is presented as documentation containing the potential for criticism. The two different strategies are presented as different ways of reconstructing and utilizing the boundary between education and art.